Kajian Meteorologi dan Oseanografi Perairan Balikpapan-Tarakan sebagai Rute Health Boat untuk Pelayanan Kesehatan Pulau Terpencil Kalimantan - Luh Putri Adnyani (LPPM ITK, 2017)
Distribution of medical facilities in Indonesia is uneven, so residents in remote islands have difficulties to reach it. We need to build health boat, a floating facility that provide standard services like in the hospital, especially in Derawan and Tarakan Islands in East Kalimantan. This Health boat has a homebase in Balikpapan. Therefore, the condition of the sea between Balikpapan, Derawan, and Tarakan need to be reviewed. One method to determine the condition of the sea is analysis of meteorological and oceanographic, which enable us to get the maximum wave height estimation. Long tern wave forecast can be obtained by using statistical methods of measurement to provide data of high wave in 1, 10, 25, 50 and 100 years.